Analysis of The Accountability of Business Actors to Consumers Who are Disadvantaged for Damage to an Item in The Context of Consumer Protection - Ni Kadek Ayu Mega Sri Deviani Putri; I Nyoman Bagiastra (Westscience Press, 2024)
This study aims to analyze the implementation of accountability from business actors to consumers who are harmed by damage to an item based on the Consumer Protection Act conducted using the literature study. The problem in this study is related to violations of rights rather than consumers for damage to an item purchased related to accountability rather than a business actor that causes these losses. The purpose of the implementation of this research is to analyze the conditions of accountability of business actors to consumers dynamics of their conditions in the territory of Indonesia. Literature study method as a method used to investigate scientific works, reports on the accountability of business actors and official documents that have a connection with the research conducted. The results showed that the accountability of business actors included compensation in the form of refund or returns to the same or equal value, but accountability still had an impact on the decline in consumer confidence in business actors. Conclusion this study states that the permeasun of legal protection efforts given to consumers for losses caused by business actors. The renewal of this research lies in the comprehensive approach used on the issues that occur and conduct in -depth research and not only look on the one hand.